2010
DOI: 10.1016/j.jcmg.2009.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Sympathetic Innervation and Long-Term Left Ventricular Mechanical Unloading

Abstract: Ventricular unloading caused clinical, functional, and hemodynamic improvements accompanied by improvements in sympathetic innervation in the failing heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 27 publications
0
47
2
4
Order By: Relevance
“…95,96 Matsui et al 97 studied patients with severe cardiomyopathy, and found that after 6 months of optimal medical therapy, a worsening H/M had, with BNP, the highest predictive value for CD, suggesting that such patients may have benefited from earlier device therapy or transplant. At the same time, a recent study by Drakos et al 98 of patients with an LVAD found that clinical improvement paralleled improvement in tracer uptake, suggesting that 123 ImIBG could guide which patients need transplant, or instead who might be able to have the device discontinued. Along the same lines, it is reported that a decreased H/M predicted poor response to CRT.…”
Section: Assessing Response To Therapymentioning
confidence: 97%
“…95,96 Matsui et al 97 studied patients with severe cardiomyopathy, and found that after 6 months of optimal medical therapy, a worsening H/M had, with BNP, the highest predictive value for CD, suggesting that such patients may have benefited from earlier device therapy or transplant. At the same time, a recent study by Drakos et al 98 of patients with an LVAD found that clinical improvement paralleled improvement in tracer uptake, suggesting that 123 ImIBG could guide which patients need transplant, or instead who might be able to have the device discontinued. Along the same lines, it is reported that a decreased H/M predicted poor response to CRT.…”
Section: Assessing Response To Therapymentioning
confidence: 97%
“…To evaluate the effects of LVAD on cardiac sympathetic innervation 123 I-MIBG imaging has demonstrated that after LVAD implantation the early and late H/M ratio increases and the washout rate decreases (70,71).…”
Section: Heart Transplantation and Left Ventricular Assist Device Impmentioning
confidence: 99%
“…123 I-MIBG imaging can also be used for assessing response to any therapies used to treat heart failure, including angiotensin-converting-enzyme inhibitors (29), angiotensin receptor blockers (30), b blockers (31), aldosterone inhibitors (32), and devices such as biventricular pacemakers for cardiac resynchronization (33) or left ventricular assist devices (34). Heart failure patients with moderate to severely reduced myocardial 123 I-MIBG uptake as a reflection of myocardial denervation have the poorest outcomes (27,28,35), in terms of morbidity and mortality from pump failure as well as from unstable arrhythmias that often precede the occurrence of sudden cardiac death (Fig.…”
Section: I-mibgmentioning
confidence: 99%